Optimasi Zink Oksida Dan Asam Malat dalam Krim Tabir Surya Kombinasi Avobenzone dan Octyl Methoxycinnamate dengan Desain Faktorial - Viddy Agustian Rosyidi; Lisanul Ummah; Nia Kristiningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Ultraviolet rays (UV) has an adverse effect on the skin, which is epidermis damage. One way to prevent the adverse effects of UV rays on the skin can be done by using sunscreen. The sunscreen mechanism of action was divided into chemical absorber and physical blocker. Chemical absorber will be degradated when exposed to UV rays, while ZnO as physical blocker can increase pH value of the sunscreen. The effectiveness of sunscreen was affected by pH value, so malic acid was added into the sunscreen formula to decrease pH value. This study was aimed to determine the optimum composition of ZnO and malic acid on pH, viscosity, SPF, transmission of erythema and transmission of pigmentation using factorial design method. 0,5% ZnO was set as the lowest level and 3% ZnO was set as the highest level; 0,5% malic acid was set as the lowest level and 0,8% malic acid was set as the highest level. Selected optimum formula was 0,5% ZnO and 0,8% malic acid with the predicted SPF value of 21,242; TE of 0,000; TP of 0,000; pH of 4,820; and viscosity of 80,333 dPa.s Keywords: sunscreen, Zinc Oxide, malic acid, Sun Protector Factor